OPTIMALISASI STRATEGI PERTOLONGAN PERTAMA PADA GAWAT DARURAT PADA MASYARAKAT DI DESA SUNGAI ALAT KECAMATAN ASTAMBUL - Annalia Wardhani (Lembaga Penelitian dan Pengabdian Masyarakat STIE Eka Prasetya, 2022)
Emergency events can occur anytime and anywhere, and require immediate treatment, because they can be life threatening or cause permanent disability. Emergency events can be caused, among others, by traffic accidents, diseases, fires and natural disasters. One of the three main pillars of the Healthy Indonesia Program is strengthening health services, including strategies to increase access to health services, optimize the referral system and improve the quality of health services, where one way is through the Integrated Emergency Management System Purpose Emergency assistance is expected to reduce the complications of a disease. This service activity is in partnership with Sungai Alat Village, Astambul District. The form of emergency first aid that can be given to prevent complications due to trauma, bleeding and shock is to provide training in first aid methods for trauma, bleeding and shock. The activity began with socialization of activities, followed by strengthening of cadres, training in emergency first aid in cases of bleeding, trauma and shock. Based on these activities, it can be concluded that after conducting emergency first aid training, the majority of participants already know the definition, purpose, benefits, indications and contraindications and procedures for carrying out emergency first aid. In addition, the majority of participants also felt enthusiastic and interested in performing emergency first aid.